Virtual sport-based positive youth development during the COVID-19 pandemic - Bates, S.; Greene, D.; O`Quinn, L. (Child and Adolescent Social Work Journal, 2021)
Sport is a foundational context for social, emotional, physical, and psychological development. The COVID-19 pandemic displaced many youth from their normative sport activities. As a result, sport-based positive-youth development (PYD) programs, typically delivered in person, had to reimagine ways to reach and engage youth in sport and life skill development. In fall 2020, The Los Angeles Football Club Youth Leadership Program (LAFC YLP) developed seven virtual sport-based PYD videos and one workshop for 120 socially vulnerable youth and their families. All virtual activities were designed to teach life skills through sport and play. Our study sought to explore the accessibility of the virtual sport-based PYD activities, the lived experiences of youth participants during lockdown, and learning outcomes of youth and families who participated in the program. We developed a mixed methods study using an online survey and virtual platform to allow youth to share photos, draw pictures, and leave comments about their lived experiences. Our findings indicated 53 youth and their families participated in the virtual sport-based PYD program and reported the activities were accessible, enjoyable, and challenging for the youth participants. In addition, 26 youth shared photos, images, or posts about their lived experiences. Our thematic analysis of the photos, images, and posts indicated the virtual sport-based PYD activities facilitated positive emotional responses, positive peer interaction, engagement with family, and utilization of environmental resources during the COVID-19 pandemic. Importantly, our findings also suggest virtual sport-based PYD activities may facilitate life skill transfer; an important developmental mechanism for learning in lieu of the decreased opportunities for sport and social interaction during the COVID-19 pandemic.